QUADRANTS OF EFFECTIVE ECONOMIC DEVELOPMENT OF UKRAINE - Kovalenko N.V. (Pressing Problems of Public Administration, 2016)
This article analyzes the issues relating to the current state of the Ukrainian economy and the transformational role of the state as an active economic entity a mixed economy. The quadrants of an effective development of the national economy are proposed for further scienti c research, which allows taking into account the sequence of changes, assets (funds), and time.